The Covid-19 Emergency and the Risk of Social Fragmentation in the Palermo Case - Siino, Antonia Roberta (Frontiers in Sociology, 2021)
The global Covid-19 crisis has shown its impact on all the aspect of life: health, social, economic, and politic. The attention mainly reserved to the economic and politic aspect musts also take into account the risk of social fragmentation. In which way this emergency has impact on communities where social fragilities already exists? In which way, social dynamics are changed by the fear of the pandemic and the physical isolation imposed to contain it. In which way local associations and citizen are coping the new challenges imposed by this emergency? In this article, the Sicilian context will be explored with a specific view on the Palermo capital. This Italian region has a peculiar and complex social asset determined by interrelated socio-economic phenomena such as mafia, unemployment and poverty. The existence of problematic and historical social phenomena has to face with the constant activities organized by local associations, civil society and authorities to fight them. There is one element that must to be consider: a global event like a pandemic oblige to be careful to the new ways in which phenomena we are accustomed to can manifest. Inequalities and racial matter can be exacerbated even in a multicultural context like Palermo one if social balance is missing. New form of poverty and the higher number of people exposed to this risk can give to mafia-type organizations more instrument to establish their control on the territory. The same introduction of economic measures aiming to support people can be manipulated and have a distorted effect when concretely applied. It is a great challenge because the lack of a complete comprehension can determine a failure of the adopted measures and a lack of cohesion of the social tissue. Starting from the context definition, the analysis will explore the perspective and the experiences of associations working with people belonging to the weaker part of the community, thanks to semi-structured interviews to representatives of the main local associations as privileged witness. In this way, the analysis will try to highlight how local actors’ activities and how dynamics of solidarity are influenced by the global Covid-19 phenomenon.